Lack of Association between MTHFR, MTR, MTRR, and TCN2 Genes and Nonsyndromic CL±P in a Chinese Population: Case-Control Study and Meta-Analysis. (September 2015) - Jiang, Chanyuan; Yin, Ningbei; Zhao, Zhenmin; Wu, Di; Wang, Yongqian; Li, Haidong; Song, Tao
Nonsyndromic cleft lip with or without cleft palate (NSCLP) is a common congenital deformity, often associated with folate deficiency. The genes MTHFR, MTR, MTRR, and TCN2 play key roles in folate metabolism. The risk of NSCLP associated with particular variants in the folic acid pathway differs among ethnic groups. The goal of this study was to explore whether genetic variations in these four genes, as well as gene-gene interactions, are associated with NSCLP. We investigated 7 tagSNPs for MTHFR, 18 tagSNPs for MTR, 15 tagSNPs for MTRR, and 7 tagSNPs for TCN2 selected from HapMap data in a Chinese population. These single nucleotide polymorphisms (SNPs) were examined for associations with NSCLP in 204 patients and 226 controls. We then performed a meta-analysis of association between rs1801133 and NSCLP. There was a significant difference in the allele frequency and haplotype analysis of rs4077829 and rs10802565 in MTR between the NSCLP and control groups but not a significant difference after correction with 10, 000 times permutations. The allele frequency, haplotype analysis, and gene-gene interactions of other SNPs did not show a significant difference. The meta-analysis results showed that no significant differences were found for allele comparison, heterozygote comparison, homozygote comparison, dominant model comparison, or recessive model comparison. The alterations of folate metabolism related to these polymorphisms are not involved in NSCLP in the Chinese population.